TCR Mechanobiology: Torques and Tunable Structures Linked to Early T Cell Signaling - Kim, Sun Taek; Shin, Yongdae; Brazin, Kristine; Mallis, Robert J.; Sun, Jim; Wagner, Gerhard; Lang, Matthew; Reinherz, Ellis L. (Frontiers in Immunology, 2012)
Recent data based upon optical tweezer experiments suggest that the TCR is an anisotropic mechanosensor, converting mechanical energy into biochemical signals upon specific peptide-MHC complex (pMHC) ligation. Tangential force applied along the pseudo-2-fold symmetry axis of the TCR complex post-ligation results in the alphabeta heterodimer exerting torque on the CD3 heterodimers as a consequence of molecular movement at the T cell-APC interface. Attendant TCR quaternary change likely fosters signaling via the lipid bilayer predicated on the magnitude and direction of the TCR-pMHC force. TCR glycans can modulate quaternary change, thereby altering signaling outcome as can the redox state of the CxxC motifs located proximal to the TM segments in the heterodimeric CD3 subunits. Predicted alterations in TCR TM segments and surrounding lipid will convert ectodomain ligation into the earliest intracellular signaling events.